2002
DOI: 10.1002/ptr.754
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic activity of Fabiana patagonica in rats

Abstract: A pharmacological evaluation of the diuretic activity of Fabiana patagonica Speg. (Solanaceae) was carried out in isotonic saline loaded rats. The data reported in the present work indicate that the acetone extract and infusion of the aerial part of Fabiana patagonica showed a moderate diuretic activity. This activity could be due, in part, to the presence of oleanolic acid isolated as the major metabolite of F. patagonica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 2 publications
(2 reference statements)
0
21
0
Order By: Relevance
“…Leaf extracts evoked no changes in diuresis or natriuresis. Whether their actives have diuretic effects need further attention (i.e., oleanolic acid, Alvarez et al, 2002Alvarez et al, , 2003Somova et al, 2003 andpolyphenols, Singh et al, 2007). Studies should also address the effect of differing doses.…”
Section: Diuretic Activitymentioning
confidence: 98%
“…Leaf extracts evoked no changes in diuresis or natriuresis. Whether their actives have diuretic effects need further attention (i.e., oleanolic acid, Alvarez et al, 2002Alvarez et al, , 2003Somova et al, 2003 andpolyphenols, Singh et al, 2007). Studies should also address the effect of differing doses.…”
Section: Diuretic Activitymentioning
confidence: 98%
“…OA is prevalent in Oleaceae family, especially in olive (O. europaea), the plant species after which the compound was named and that still serves as the main source of commercial OA (Pollier & Goossens, 2012;Sporn et al, 2011). Many pharmacological activities of OA have been reported such as antifungal (Tang et al, 2000), insecticidal (Marquina et al, 2001), anti-HIV (Ma et al, 2000), diuretic (Alvarez et al, 2002), complement inhibitory (Assefa et al, 2001), liver-protection (Yim et al, 2001), anti-inflammatory (Ismaili et al, 2001) and gastrointestinal transit modulating activities (Li et al, 1999). In recent years, it was found that OA exhibited the significant antitumor effect and cytotoxic activity toward many cancer cell lines such as liver cancer cells, colon carcinoma cells and fibrosarcoma cells (Li et al, 2002;Yan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(bolsa de pastor) a plant native to Brazilian Cerrado, extends beyond the phytotherapeutic use. Its leaves produce ursolic, oleanolic and betulic acids, pentacyclictriterpenoids, with validated biological properties, such as anticancer activity [1], inhibitory effects on NO production and iNOS induction [2], anti-inflammatory [3], antifungal [4], diuretic [5]. Ethanol extract from Z. montana leaf possesses anti-nociceptive [6] and anti-inflammatory [7] activities and flavanones showed cytotoxicity against human NCI-ADR/RES and K562 cell lines [8].…”
Section: Introductionmentioning
confidence: 99%